(untitled) (University of Thi-Qar Journal for Engineering Sciences, 2013)
Experimental and numerical investigation of a high speed centrifugal pump has been carried out. In experimental work, a test rig which includes a centrifugal pump, fast response piezoelectric pressure transducers, Rota meter flow and measurement instrumentations is designed and constructed. Two impellers having different outlet diameters were examined for the same volute. A data acquisition system (hardware) and its software (Visual Basic language) have been developed to analyze the pressure transducer signal in order to obtain the pressure fluctuations. The governing partial differential equations (continuity, momentum) besides to turbulence model are discretized to algebraic equations by using finite volume method. The solution of these equations was done by using FLUENT 6.3 commercial code. This code has the ability to use a grid generation technique and transform the physical domain to a computational domain by using GAMBIT 2.2.3 software. The effect of turbulence was simulated by using a standard k-e model. The wall function laws are used to remedy the regions near the rotating and volute walls. The effect of angular position of impeller and impeller’s diameter on the flow behavior is studied for different values of volume flow rate. The obtained results show that the pressure fluctuations registered in the volute were found to be very dependent on both angular position and volume flow rate. It is observed that the pressure fluctuations have maximum values at volume flow rate (Q=0.5QN) for the considered two impellers at angular position (?= 270o). These values increase as impeller diameter increases. The results also show that the higher static pressure values are observed upstream of the leading edge at the volute tongue (stagnation point) while the minimum was found at impellers eye. A comparison between experimental and numerical results is done and the agreement was acceptable.